Analysis of the Pomelo Peel Essential Oils at Different Storage Durations Using a Visible and Near-Infrared Spectroscopic on Intact Fruit - Panmanas Sirisomboon; Jittra Duangchang; Thitima Phanomsophon; Ravipat Lapcharoensuk; Bim Prasad Shrestha; Sumaporn Kasemsamran; Warunee Thanapase; Pimpen Pornchaloempong; Satoru Tsuchikawa (My University, 2024)
Pomelo fruit pulp mainly is consumed fresh and with very little processing, and its peels are discarded as biological waste, which can cause the environmental problems. The peels contain several bioactive chemical compounds, especially essential oils (EOs). The content of a specific EO is important for the extraction process in industry and in research units such as breeding research. The explanation of the biosynthesis pathway for EO generation and change was included. The chemical bond vibration affected the prediction of EO constituents was comprehensively explained by regression coefficient plots and x-loading plots. Visible and near-infrared spectroscopy (VIS/NIRS) is a prominent rapid technique used for fruit quality assessment. This research work was focused on evaluating the use of VIS/NIRS to predict the composition of EOs found in the peel of the pomelo fruit (
Keywords: Spectroscopy and Chemometric Analyses